Effect of temperature on germination and initial growth of seeds of Capsicum frutescens (L.) - Teixeira, Sheila Bigolin (2018)
The temperature oscillation, provoked by the climatic changes, has been affecting the agriculture in several points of agricultural areas, with that, it is necessary to carry out studies on the adaptability of the crops to a wide range of temperature. Thus, the objective of the study was to verify the efficiency of the germination and initial establishment of chilli pepper seedlings submitted to sub and supra optimal temperatures. The experiment was conducted in a completely randomized experimental design, in a factorial scheme consisting of one species and three temperatures (15 ° C, 25 ° C and 35 ° C). The seeds were submitted to germination tests, under a photoperiod of 12 hours for 14 days, together with first germination count, germination speed index, seedling length, total dry mass, electrical conductivity, respiratory activity and imbibition curve under the temperatures of 15, 25 and 35 °C. The temperature of 25 ° C presented superiority to the other treatments in all variables tested. At temperatures of 15 and 35 ° C, germination was completely inhibited. Tests such as those performed in the present study are efficient for the determination of seed viability in different temperature ranges.